2020
DOI: 10.35219/foodtechnology.2020.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the extraction method on physico-chemical proprieties, phytochemicals and biological activity of sesame seeds oil

Abstract: This study aimed at characterizing oil extracted from roasted and unroasted sesame seeds (Sesamum indicum L.) following either Soxhlet using hexane as the solvent or cold pressing. We obtained an inverse relationship between oil yield and seed moisture content. Seed roasting as well as Soxhlet extraction improved oil yield. Specific absorptivity (at 232 and 270 nm) increased with heating treatment. Refractive values of the different oils were about 1.464. Peroxide value was 7.6 to 9.6 meq O 2 /kg, iodine value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Roasting the seeds has been shown to increase the oil yield and improve the antioxidant properties of the oil extract [12]. However, it has also been observed that roasting and dehulling seeds can reduce the lignan and phenolic compounds content, which are important for the antioxidant activity of sesame extracts [250]. On the other hand, processing treatments such as soaking, cooking, germination, fermentation, and microwave heating have been found to reduce the phenolic compounds and tannins content in oilseeds, including sesame seeds [251].…”
Section: Processing Technology Of Sesamementioning
confidence: 99%
“…Roasting the seeds has been shown to increase the oil yield and improve the antioxidant properties of the oil extract [12]. However, it has also been observed that roasting and dehulling seeds can reduce the lignan and phenolic compounds content, which are important for the antioxidant activity of sesame extracts [250]. On the other hand, processing treatments such as soaking, cooking, germination, fermentation, and microwave heating have been found to reduce the phenolic compounds and tannins content in oilseeds, including sesame seeds [251].…”
Section: Processing Technology Of Sesamementioning
confidence: 99%
“…Density A substance's density is defined as its mass/volume ratio. Seed and vegetable oils vary in density according to temperature, minor components, and the content of fatty acids [14]. Based on the data in Table 3.1, the density of sesame seed was determined to be 0.950±0.018d.…”
Section: Moisture Contentmentioning
confidence: 99%
“…For specific absorptivity measurement, 2.5g of sample oil was adjusted to 25ml with cyclohexane and homogenized [15]. Absorbance was measured at 232 and 270nm in a spectrophotometer (Uvline 9400, Secomam, France).…”
Section: Specific Absorptivitymentioning
confidence: 99%